تصميم المرشحات المستخدمة للحد من التوافقيات في الشبكات الكهربائية الصناعية - جـبل, فـؤاد (Latakia University Journal -Engineering Sciences Series, 2019)
الهدف من البحث هو وضع نموذج رياضي وتنفيذ برنامج على الحاسب الآلي يمكن استخدامه بسهولة لتصميم المرشحات الأحادية التوليف المستخدمة للحد من تأثير التوافقيات العليا في الشبكات الكهربائية الصناعية وخاصة على مكثفات تحسين عامل الاستطاعة . تم الأخذ بالاعتبار أثناء التصميم المعايير الدولية التي تعطي القيم الحدية المسموح تطبيقها على المكثفات ، إضافة إلى استطاعة المرشح ونقطة الرنين وتوليف المرشح وأثر الانحرافات الناتجة عن الاختلاف في درجات الحرارة والتردد والتصنيع على توليف المرشح . The objective of this paper is to present a mathematical model and implement a PC program that can easily be used for designing single-tuned filters to limit the effect of high harmonics on industrial and electrical networks, especially on power factor capacitors. During the design process, the international standards giving the permissible limiting values applicable to capacitors have been taken into account, in addition to: filter power, resonance point, filter tuning, and the effect of variation resulting from manufacturing, frequency, and temperatures on filter tuning.